Bottle-feeding practice and its associated factors among mothers of children aged 0 to 23 months in sub-Saharan Africa: a multi-level analysis of demographic and health surveys (2015-2022) - Enyew Getaneh Mekonen (BMC, 2024)
Abstract Background Avoidance of bottle feeding is recommended as it interferes with optimal suckling behavior, is difficult to keep clean, and is an important route for the transmission of pathogens. However, there is a current shift towards breastfeeding for a short period and the introduction of bottle feeding in both the developed and developing worlds. Bottle-feeding practice and its individual- and community-level determinants are not addressed in sub-Saharan Africa. Therefore, this study aimed to fill this gap and assess the pooled prevalence and associated factors of bottle feeding among mothers of children less than 23 months of age. Methods Data from the recent demographic and health surveys of 20 countries in sub-Saharan Africa conducted between 2015 and 2022 were used. A total weighted sample of 86,619 mother-child pairs was included in the current study. Multilevel mixed-effects logistic regression was used to determine the factors associated with the outcome variable. Intra-class correlation coefficient, likelihood ratio test, median odds ratio, and deviance (-2LLR) values were used for model comparison and fitness. Finally, variables with a p-value < 0.05 and an adjusted odds ratio with a 95% confidence interval were declared statistically significant. Results The overall pooled prevalence of bottle feeding among mothers of children aged 0 to 23 months in sub-Saharan Africa was 13.74% (95% CI: 13.51%, 13.97%). Factors like maternal age [AOR = 1.09; 95% CI (1.04, 1.14)], educational status [AOR = 2.83; 95% CI (2.58, 3.10)], marital status [AOR = 1.16; 95% CI (1.09, 1.24)], maternal occupation [AOR = 0.76; 95% CI (0.73, 0.79)], media exposure [AOR = 0.80; 95% CI (0.76, 0.85)], wealth index [AOR = 1.21; 95% CI (1.15, 1.29)], sex of the household head [AOR = 1.17; 95% CI (1.12, 1.24)], family size [AOR = 1.06; 95% CI (1.01, 1.12)], number of under-five children [AOR = 1.11; 95% CI (1.04, 1.19)], place of delivery [AOR = 1.06; 95% CI (1.00, 1.12)], mode of delivery [AOR = 1.41; 95% CI (1.31, 1.52)], counseling on breastfeeding [AOR = 0.88; 95% CI (0.84, 0.92)], age of the child [AOR = 1.65; 95% CI (1.57, 1.75)], and residence [AOR = 1.64; 95% CI (1.56, 1.72)] were significantly associated with bottle-feeding practices. Conclusion Nearly one out of seven children aged 0 to 23 months received bottle feeding in sub-Saharan African countries. Older mothers, higher mothers' educational status, unmarried women, richest families, non-working mothers, exposed to media, female-headed households, large family size, having one under-five children, home delivery, cesarean delivery, children aged 6-11 months, and urban residence were significantly associated with an increased risk of bottle feeding. Breastfeeding promotion programs are advised to target mothers who are older, educated, working, rich, gave birth at home, have a large family size, are delivered by cesarean section, have children aged 6-11 months, and reside in urban areas to achieve a significant decrease in bottle feeding rates in sub-Saharan Africa.